BER analysis of space‐time coded RFID system in Nakagami‐m fading channels. Issue 5 (1st February 2014) - Maichalernnukul, K.; Zheng, F.; Kaiser, T.
Abstract : The exact bit error rate (BER) analysis of a space‐time coded radio frequency identification (RFID) system is presented, where the tag has multiple antennas and the reader has a single antenna. In the analysis, the forward and backward channels exhibiting independent but not necessarily identically distributed Nakagami‐ m fading are considered, and the diversity order that the system can achieve is found to be N min( m h, m g ), where N is the number of antennas at the tag and m h and m g are the fading parameters corresponding to the forward and backward channels, respectively. The analytical results are verified through comparison with the simulation results.